Lingkungan Kewirausahaan dalam Motivasi Berwirausaha - Tammie, Rieke Amaluthvie; Nuryanti, B Lena; Utama, R Dian H (Business Education Program of Universitas Pendidikan Indonesia, 2019)
ABSTRACTThis study aims to determine the effect of entrepreneurial environment to entrepreneurial motivation. This research uses descriptive approach with explanatory survey method. The student analysis unit is 167 people . Data collection using questionnaire. The analysis technique used is verifikative technique by using frequency distribution. The result showed that entrepreneurial environment enough effected on entrepreneurial motivation. The differences in this study located on an object research, time research, a measuring instrument , literature that used , the theory that is used and the results of the study Keywords: entrepreneurial envriontmen; entrepreneurial motivation ABSTRAKPenelitian ini bertujuan untuk mengetahui seberapa besar pengaruh lingkungan kewirausahaan terhadap motivasi berwirausaha. Penelitian ini menggunakan pendekatan verifikatif dengan metode explanatory survey. Unit analisis siswa sebanyak 167 orang. Pengumpulan data dengan menggunakan kuesioner. Teknik analisis yang digunakan adalah teknik verifikatif dengan menggunakan distribusi frekuensi. Hasil penelitian menunjukan lingkungan kewirausahaan memiliki pengaruh cukup terhadap motivasi berwirausaha.